Coco Stretch: Strain Sensors Based on Natural Coconut Oil and Carbon Black Filled Elastomers. Issue 2 (10th December 2020) - Lugoda, Pasindu; Costa, Júlio C.; Garcia‐Garcia, Leonardo A.; Pouryazdan, Arash; Jocys, Zygimantas; Spina, Filippo; Salvage, Jonathan; Roggen, Daniel; Münzenrieder, Niko
Abstract: A biocompatible inexpensive strain sensor constituting of an elastomer filled with natural coconut oil (CNO) and carbon black (CB) is presented here. Strain sensors are widely utilized for applications in human activity recognition, health monitoring, and soft robotics. Given that these sensors are envisioned to be present in a plethora of fields, it is important that they are low cost, reliable, biocompatible, and eco‐friendly. This work demonstrates that CNO can be used to create conductive percolation network in elastomers, without the necessity for harmful chemicals or expensive machinery. The sensor has a gauge factor of 0.77 ± 0.01, and the sensing material has a porous morphology filled with an oily suspension formed of CNO and CB. Results indicate that the liquid filled porous structure can improve the reliability of these resistive strain sensors in comparison to sensors fabricated utilizing commonly used non‐polar solvents such as heptane. Consequently, the sensor demonstrates a hysteresis of only 2.41% at 200% strain over 250 stretch/release cycles. Finally, to demonstrate the potential of this fabrication technique, a functionalized glove is developed and used to detect wrist motion. These easily manufacturable and cost‐effective sensors enable wearable on‐skin ergonomic intervention systems with minimal impact on the environment. Abstract : A biocompatible inexpensive strain sensor constituting of an elastomer filled with natural coconut oil and carbon black is presented here. The easily manufacturable and eco‐friendly fabrication technique enables the creation of strain sensors in environments where standard electronic/chemical fabrication facilities are unavailable, like in schools and developing countries. These devices stretch to 1035% and is utilized for wrist motion detection.